2019
DOI: 10.1186/s13578-019-0342-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is among the most prevalent and lethal cancers in the human population. HCC is an inflammation-associated cancer caused by different etiological factors. The chronic inflammation leads to continuous cycles of hepatocytes destructive-regenerative process and contributes to HCC initiation and progression. Macrophages play a crucial role in chronic liver inflammation. The tumor microenvironment plays a key role in the progression of HCC. Tumor-associated macrophages are a well-known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 118 publications
1
93
0
Order By: Relevance
“…Neutrophils contribute to the activation, regulation and effector function of immune cells [37]; they are also capable of HCC progression by secreting a wide range of cytokines [38], thereby demonstrating their crucial role in the pathogenesis of HCC. A number of studies have reported that increased macrophages were related to poor prognosis in HCC [39]. Macrophages infiltration within the tumor microenvironment could facilitate tumor growth, angiogenesis, invasion, as well as metastasis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils contribute to the activation, regulation and effector function of immune cells [37]; they are also capable of HCC progression by secreting a wide range of cytokines [38], thereby demonstrating their crucial role in the pathogenesis of HCC. A number of studies have reported that increased macrophages were related to poor prognosis in HCC [39]. Macrophages infiltration within the tumor microenvironment could facilitate tumor growth, angiogenesis, invasion, as well as metastasis [40].…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear transcription factor, HIF-1α, is a crucial biomarker of the hypoxia tumor microenvironment, which is due to the rapid proliferation of tumor cells [27]. Studies have reported that HMGB1 recruited macrophages into HCC tissue via HIF-1α, or HMGB1-regulated HIF-1α to promote the tumor malignancy [28,29]. It can be seen that HMGB1 and HIF-1α act as partners in promoting cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the intramural neutrophil infiltration is elaborated to be promoted by the CXCL5 and CXCR2-CXCL1 axis; besides, it displays marked correlation with shorter OS and HCC recurrence, and serves as an independent prognostic factor [32][33][34]. Moreover, the increased infiltration of tumor-associated macrophages dominated by the M2 macrophages, which may be ascribed to the deletion of the Hippo signaling, has been reported to produce the Wnt/β-catenin signaling and trigger the elevated intramural FoxP3+ Treg population, while this in turn accelerates HCC progression [35][36][37]. In addition, accumulating evidence reveals a role of DCs as an adverse prognostic factor for HCC.…”
Section: Discussionmentioning
confidence: 99%